Stigma consciousness among the unemployed and prejudices against them: development of two scales for the 7th wave of the panel study “Labour Market and Social Security (PASS)” - Thomas Gurr; Monika Jungbauer-Gans (Journal for Labour Market Research, 2013)
This paper develops scales to measure stigma consciousness in the unemployed and prejudices against them, using a quantitative survey. The requirement for these scales is illustrated in the introduction. The theoretical substantiation of the scale development includes a definition of stigmatisation, an overview of the current state of research regarding the consequences of stigmatisation for individuals, and the possible causes of stigmatisation processes. The argumentation is based on reflections on the significance of employment in people's lives. How the prejudice and the stigmatisation scales are developed is the subject-matter of the main section. Using data from a pre-test of both scales, the final version of the scales is then carved out. We conclude with a summary of our theoretical considerations and some thoughts about possible applications for the scales.
Keywords: 330; IAB-Haushaltspanel; Arbeitslose; Stigmatisierung - Messung; Wahrnehmung; Skalierung; Stigmatisierung - Auswirkungen; Stigmatisierung - Ursache; Vorurteil; Forschungsstand; Fragebogen; Fremdbild; Stereotyp; Diskriminierung; soziale Ausgrenzung; Selbstbewusstsein